FRAKSI AIR DAUN UBI JALAR (Ipomea batatas (L.) Lam) SEBAGAI HEPATOPROTEKTOR TERHADAP TIKUS PUTIH JANTAN YANG DIINDUKSI PARACETAMOL - Lilik Koernia Wahidah; Ramadhan Triyandi; Rima Indriani (JFL : Jurnal Farmasi Lampung, 2019)
Sweet potato leaves (Ipomea batatas (L) Lam ) are empirically used by people in some regions as traditional medicines to treat dengue fever and as anti-cancer because of their high antioxidant content. This study aims to see the effect of sweet potato leaf water fraction as a hepatoprotector on male white rats induced by paracetamol. Sweet potato leaves were extracted by maceration using 70% ethanol for 8 days then fractionation was carried out. The hepatoprotector test was carried out on 25 rats grouped in 5 groups treated orally for 7 days, namely negative controls given aquades, positive controls were given hepamax dose 59.06 mg / kgBB, groups I, II and III were given a fraction of sweet potato leaf water with a dose of 4.77 mg / kgBB, 9.54 mg / kgBB, and 19.08 mg / kgBB then male white rats induced by paracetamol orally at a dose of 1350mg / kgBB for 1 day. The increase in SGPT and SGOT levels was measured on day 9 using spectrophotometry then analyzed by ANOVA method. The results of SGPT analysis showed that groups I, II and III were significantly different from the negative controls (sig 0,000), and had the same effect on positive controls (sig 0.144) in suppressing SGPT level increases while in the analysis results the SGOT group III levels were significantly different from controls negative (sig 0,000) and significantly different from group I, II (sig 0.30 and 0.24), and have the same effect as positive controls (sig 0.392). The third dose (19.08 mg / kgBB) showed the best suppression increased and was not significantly different from statistically positive controls. Based on the research it was concluded that the fraction of sweet potato leaf water could be used as a hepatoprotector for male white rats induced by paracetamol. Keywords: Hepatoprotector, Paracetamol, Sweet Potato Leaves.